Pancreatic Cancer Insights into Molecular Mechanisms and Novel Approaches to Early Detection and Treatment - McCall, Kelly (IntechOpen, 2014)
This book provides the reader with an update on recent findings related to the molecular basis for the development and progression of pancreatic cancer. This book also informs the reader about the link between obesity and pancreatic cancer, and how a well-known and widely used anti-diabetic drug may also be potentially useful for the treatment of pancreatic cancer. Moreover, this book provides insight into novel approaches for improved earlier detection of pancreatic cancer.